Statistical modelling for the source rock parameters of the montney formation, ne british columbia, canada - Barham, A. (MDPI, 2022)
Hydrocarbons in self-sourced reservoirs are determined by the concentration and maturation of organic matter in sediments. As a result, lowering risk in unconventional resource research and development requires knowledge of hydrocarbon potentiality factors. The geochemical data for the Montney Formation samples studied suggest that it is a fair to good source rock with type IV kerogen that can generate gas in general. The statistical modelling of the analyzed data reveals a valuable technique for identifying characteristics, clusters, and linkages that affect source rock assessment. The Spearmanâs correlation coefficient showed a good positive correlation between the total organic carbon (TOC) and free hydrocarbons (S1 ), generating potential (S2 ), and potential yield (GP). There was a weak correlation with the maturity index (Tmax) and hydrogen index (HI) and a highly negative correlation between the TOC and oxygen index (OI). On the other hand, the principal component analysis (PCA) showed the presence of three factors affecting the source rock evaluation. Factor 1 included TOC, S1, and S2, which are related to organic richness and hydrocarbon potentiality; factor 2 contained the production index (PI), and the generated CO2 (S3 ) was related to the organic matter source. Factor 3 included the Tmax and HI related to the type of organic matter and thermal maturity. In addition, the TwoStep cluster analysis separated the source rock in the study area into two major groups. Cluster 1 is characterized relatively by high HI, TOC, S1, S2, and PI, with Tmax < 455â¦C indicating good source rock in the mature level with the capability to generate little oil and condensate gas. Cluster 2 is characterized by relatively low HI, TOC, S1, S2, and PI, with Tmax > 455â¦C, indicating an over-mature source rock in the dry gas window. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.